The Marind Tribe’s Behavior in Cultivating Paddy Field in Merauke Regency, Papua Province - Yolanda Holle (Jurnal Penyuluhan, 2020)
The focus of this study was to observe the behavior of the Marind Tribe in cultivating paddy field. The study intended to develop lowland rice by paying attention to the behavior of the Marind Tribe as agribusiness actors. This study aims to analyze the knowledge, attitudes, forms of action of Marind tribe farmers in rice farming and analyze the rice production produced. This research was conducted in Merauke Regency as a center for rice production in the province of Papua. The method used in this study is a survey method with in-depth interview techniques and observations of 120 Marind farmers who work on lowland rice in six districts in Merauke Regency. Data were analyzed using descriptive statistical analysis and inferential statistics. The results of the study concluded: (1) the knowledge of the Marind Tribe is still in the basic realm of knowing; (2) the Marind Tribe is hesitant to apply the cultivation of lowland rice; (3) the form of actions for planting lowland rice is incomplete; and (4) the level of production of lowland rice produced is very low.